Sanksi terhadap Pelanggaran Konservasi Taman Hutan Raya R. Soerjo di Mojokerto - Zulaihah, Zulaihah (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2014)
Abstract: This paper focuses on the concept of criminal (jinayah) jurisprudence toward the sanction of the conservational violation of the Taman Hutan Raya R.Soerjo (TAHURA R.Soerjo) according to Undang-Undang No. 41 tahun 1999 on Forestry. This is a qualitative research and will be analyzed descriptively with deductive framework. Some of the conservational violations in the Taman Hutan Raya R.Soerjo are entering the forest, harvesting or collecting the forests product, shepherding cattle in the forest area, damaging forest, and logging which is conducted by the surrounding community. The violations are described in article 50 Undang-Undang No. 41 tahun1999 on forestry. Penalty for violation of TAHURA R.Soerjo in SKPPKH Mojokerto region given by the local officer is in the form of guidance, warning, making a statement not to repeat the action for the second offense. However, it will be directly handed over to the police if the evidence has been sufficient. Sanction for such violations will be given by the competent authority in accordance with the legislation. The sentence is in accordance with article 78 and 79 Undang-Undang No. 41 tahun 1999. The sanction of the conservational violation of the Taman Hutan Raya R.Soerjo, in Islamic criminal law, is a part of tazir because it has not reached a nishab of theft. Keywords: Jurisprudence, jinayah, sanction, violation, conservation